Implementasi Konsep Sajidin Dalam Surat Al-Hijr Ayat 98 Pada Dunia Pendidikan - Istiqomah rahmawati; Eko Ngabdul Shodikin; Sarwadi (At Turots: Jurnal Pendidikan Islam, 2022)
The word prostration in the Qur'an with its various forms, often experiences repetition in many verses, this indicates that the word has an important and deep meaning. This is what inspired the author to explore the concept of "sajidin" in the letter al Hijr verse 98 "wa kun minas sajidin" which means "be you among those who prostrate". The secret behind Allah's command in this verse will be discussed in this paper. The origin of the word sajidin is the plural form of sa>jid which means perpetrator. Prostrating means prostrating the noblest part parallel to the ground. Everything in nature prostrates to Allah in their respective situations and conditions, starting from plants, animals and even heavenly bodies. When a person prostrates, he prostrates his face at the level of his feet. This has a deep philosophical meaning, there is helplessness, the totality of surrender, submission and so on. The author tries to reveal the concept to adopt its values ​​so that it can be implied in the educational process in the hope that generations of sajidi>n mentality will be born.